Flagellar Motility Is Critical for Salmonella enterica Serovar Typhimurium Biofilm Development - Wang, Feiying; Deng, Le; Huang, Fangfang; Wang, Zefeng; Lu, Qiujun; Xu, Chenran (Frontiers in Microbiology, 2020)
The food-borne pathogen Salmonella enterica serovar Typhimurium (S. Typhimurium) causes self-limiting gastroenteritis in humans, and is not easily eradicated because it often attaches to suitable surfaces to form biofilms that have high resistance to disinfectants and antimicrobials. To develop an alternative strategy for the treatment of biofilms, it is necessary to further explore the effects of flagellar motility on the development process of Salmonella biofilms. Here, we constructed flagella mutants (ΔflgE and ΔfliC) to systematically study this process. By comparing them with wild-type strains, we found that these mutants lacking flagellar motility form fewer biofilms in the early stage, and the formed mature biofilms contain more cells and extracellular polymeric substances (EPS). In addition, fewer mutant cells adhered to glass plates compared with wild-type cells even after 6 h of incubation, suggesting that flagellar motility play a significant role in preliminary cell-surface interactions. More importantly, the motility of wild-type strain was greatly decreased when they were treated with carbonyl cyanide m-chlorophenylhydrazone, which inhibited flagellar motility and reduced biofilm formation, as in the case of the ΔflgE mutant. Overall, these findings suggest that flagellar motility play an important role in Salmonella biofilm initiation and maturation, which can help us to counteract the mechanisms involved in biofilm formation and to develop more rational control strategies.